2014
DOI: 10.5194/bg-11-613-2014
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Disturbance of soil structure can lead to release of entrapped methane in glacier forefield soils

Abstract: Abstract. Investigations of sources and sinks of atmospheric CH4 are needed to understand the global CH4 cycle and climate-change mitigation options. Glaciated environments might play a critical role due to potential feedbacks with global glacial meltdown. In an emerging glacier forefield, an ecological shift occurs from an anoxic, potentially methanogenic subglacial sediment to an oxic proglacial soil, in which soil-microbial consumption of atmospheric CH4 is initiated. The development of this change in CH4 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Moreover, a seemingly widespread CH 4 source was discovered during a field survey on CH 4 turnover in sediments of five Swiss glacier forefields situated on calcareous bedrock (Nauer et al, ). Subsequent analyses confirmed that this CH 4 was entrapped in the sediment matrix and could be released upon acidification or mechanical impact (Nauer et al, ). As measurements had indicated oxic conditions and low organic carbon (OC) content in these sediments, ongoing microbial CH 4 production was considered unlikely (Nauer et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, a seemingly widespread CH 4 source was discovered during a field survey on CH 4 turnover in sediments of five Swiss glacier forefields situated on calcareous bedrock (Nauer et al, ). Subsequent analyses confirmed that this CH 4 was entrapped in the sediment matrix and could be released upon acidification or mechanical impact (Nauer et al, ). As measurements had indicated oxic conditions and low organic carbon (OC) content in these sediments, ongoing microbial CH 4 production was considered unlikely (Nauer et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…As our measurements represent net fluxes, i.e., the sum of simultaneous CH 4 transport, production, and consumption (53), differences in any of these processes may explain differences in CH 4 flux between the landforms. Although we were unable to distinguish between individual processes, occasionally observed CH 4 emissions at locations F and T support the presence of a CH 4 source of as yet unknown origin in these calcareous glacier forefield soils (54). We found no evidence of microbial CH 4 production on screening of the top 15 cm of soils at locations S, F, and T for presence of the mcrA gene, a biomarker for methanogenic Archaea (data not shown).…”
Section: Chiri Et Al Applied and Environmental Microbiologymentioning
confidence: 62%
“…It may indicate that Methylocystis-like MOB possess an ecological advantage in calcareous glacier forefield soils, which may be linked to the existence of two pMMO isoenzymes, with different affinities for low (2 to 600 l liter Ϫ1 ) and high (Ͼ600 l liter Ϫ1 ) CH 4 concentrations, previously detected in cultures of a Methylocystis strain (11). Thus, Methylocystis-like MOB may profit from transient release of CH 4 (at elevated concentrations) entrapped in calcareous soil aggregates (54).…”
Section: Chiri Et Al Applied and Environmental Microbiologymentioning
confidence: 88%
See 2 more Smart Citations